The Dictionary of Feminist Theory - Humm, Maggie (Edinburgh University Press, 2003)
The most comprehensive guide to the terminology and history of feminist theory available.This established and much admired dictionary provides succinct definitions of more than 600 terms, topics, movements and approaches as well as influential feminist thinkers, activists and critics within feminist theory. Entries cover a wide range of cross-cultural issues relating to family, work, sexuality, gender, race, imperialism and representation. There are also explanations of terms within Anglo-American and French feminist literary theory that have come into common usage, including 'Backlash', 'Postcolonialism', 'Postmodernism' and 'Queer Theory'. From 'Autobiography' to 'Writing the Body', from 'Abortion' to 'Work' and from 'Anzaldua' to 'Zimmerman', the Dictionary is a valuable source for anyone interested in the ideas behind feminism or those approaching contemporary feminist thought for the first time.